Punching above One's Weight: The Case against Election Campaigns - Marco A. Haan; Bart Los; Sander Onderstal; Yohanes E. Riyanto (Tinbergen Institute, 2010)
Politicians differ in their ability to implement some policy. In an election, candidates make commitments regarding the plans they will try to implement if elected. These serve as a signal of true ability. In equilibrium, candidates make overambitious promises. The candidate with the highest ability wins. Yet, the electorate may be better off having a random candidate implement her best plan, rather than seeing the winner implementing an overambitious plan. This is more likely if the ability distribution is skewed toward high values, the number of candidates is high, with private benefits from being elected, or if parties select candidates.
Keywords: D72; 330; election promises; signalling; Politisches Ziel; Politiker; Meinung; Wahlkampf; Signalling; Neue politische Ökonomie